Byte by byte: Influence of content generator - Investigating the impact of AI-generated content on health outcomes - Gonçalves, Armindo Pereira (2024)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Driven Marketing, specialization in Marketing Intelligence